PENINGKATANÃÂ HASILÃÂ BELAJARÃÂ SISTEMÃÂ PENGAPIANÃÂ FULLÃÂ TRANSISTOR MENGGUNAKANÃÂ MEDIAÃÂ PERAGAÃÂ DISTRIBUTORÃÂ BOARDÃÂ PANELÃÂ ÃÂ ÃÂ - RubaiÃƒÂ‚Ã‚Â WijayaÃƒÂ‚Ã‚Â , M.ÃƒÂ‚Ã‚Â BurhanÃƒÂ‚Ã‚Â ; DoniÃƒÂ‚Ã‚Â WidodoÃƒÂ‚Ã‚Â , RahmatÃƒÂ‚Ã‚Â (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Negeri Semarang, 2010)
Penelitian ÃÂ ini ÃÂ bertujuan ÃÂ untuk ÃÂ membuat ÃÂ media ÃÂ peraga ÃÂ distributor ÃÂ board ÃÂ panel ÃÂ dan ÃÂ mengetahuiÃÂ peningkatan hasil belajar mahasiswa tentang sistem pengapian ÃÂ full transistor setelah menggunakan media peragaÃÂ tersebut. Penelitian ini menggunakan desain eksperimen semu/Quasi Experiment Design dengan pola pre testÃÂpostÃÂ test ÃÂ one ÃÂ group ÃÂ design. Populasi penelitian ÃÂ ini ÃÂ adalah 100 ÃÂ orang mahasiswa program diploma ÃÂ (D3) Teknik MesinÃÂ Universitas ÃÂ Negeri ÃÂ Semarang ÃÂ yang ÃÂ mengikuti ÃÂ matakuliah ÃÂ kelistrikan ÃÂ otomoti ÃÂ ftahun ÃÂ ajaran ÃÂ 2009/2010 ÃÂ yangÃÂ terbagi dalam 3 ÃÂ rombongan belajar ÃÂ (rombel). Satu ÃÂ rombel ÃÂ (rombel 02) dengan 36 orang dijadikan ÃÂ sampel. HasilÃÂ penelitian menunjukkan ÃÂ adanya peningkatan hasil belajar ÃÂ sistem ÃÂ pengapian ÃÂ full ÃÂ transistor ÃÂ setelah menggunakanÃÂ media peraga. Nilai rataÃ¢â¬Ârata pre test sebelum menggunakan media peraga sebesar 44,46 dan setelah menggunakanÃÂ media peraga (post test) sebesar 72,42. Nilai mahasiswa mengalami peningkatan 55,94 %.Kata kunci: peningkatan hasil belajar, media peraga distributor board panel, sistem pengapian full transistorÃÂ The ÃÂ objectives ÃÂ of ÃÂ the ÃÂ research ÃÂ are ÃÂ to make distributor board panel medium ÃÂ and ÃÂ to ÃÂ identify ÃÂ the ÃÂ resultÃÂ learning ÃÂ improvement about ÃÂ full ÃÂ transistor ignition system after the use of the mentioned medium. This researchÃÂ uses quasi experiment design with pre testÃÂpost test one group design pattern. The population of this research wasÃÂ about 100 students of diploma program (D3) of Mechanical Engineering Department of Semarang State UniversityÃÂ (UNNES) ÃÂ that ÃÂ joined automotive electricity subject year 2009/2010 that was categorized ÃÂ into 3 ÃÂ learning groups ÃÂ .ÃÂ One learning group (group 2) with 36 students was taken to be sample. The result of the research shows theÃÂ learning result ÃÂ improvement of ÃÂ full ÃÂ transistor ignition system after the use of visual display or medium. The rateÃÂ score of pre test before the use of the medium is about 44,46 and after the use of it (post test) the rate is aboutÃÂ 72,42. The scores of students get improvement about 55,94%.Keywords: the learning result improvement, distributor board panel medium, full transistor ignition system